2020
DOI: 10.1039/d0nr05968d
|View full text |Cite
|
Sign up to set email alerts
|

Nanonet-nano fiber electrospun mesh of PCL–chitosan for controlled and extended release of diclofenac sodium

Abstract: Electrospun nanofiber (EN) technology has been used in the past to generate electrostatically charged multilayer-nanofibers. This platform offers versatile applications including in tissue engineering, drug delivery, wound dressings, and high-efficiency...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Due to this fact, PCL is one of the most used synthetic polymers for medical applications, such as controlled drug delivery or release systems with a single bolus administration [1,2], as well as wound dressing [3,4] or regenerative tissue engineering [5,6]. Release systems, or drug delivery vehicles, have received increased attention in pharmaceutical treatment because they afford several advantages compared to conventional forms of dosage, including enhanced therapeutic efficacy and low toxicity when the drug is released at a controlled rate [7][8][9][10][11]. The release time of the drug needs to be prolonged for days or even several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this fact, PCL is one of the most used synthetic polymers for medical applications, such as controlled drug delivery or release systems with a single bolus administration [1,2], as well as wound dressing [3,4] or regenerative tissue engineering [5,6]. Release systems, or drug delivery vehicles, have received increased attention in pharmaceutical treatment because they afford several advantages compared to conventional forms of dosage, including enhanced therapeutic efficacy and low toxicity when the drug is released at a controlled rate [7][8][9][10][11]. The release time of the drug needs to be prolonged for days or even several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the release rate of ketoprofen revealed no significant difference on pristine and plasma-treated PCL membranes. Diclofenac sodium(DS) combined with an electrospinning nano-and-nanofiber (DS-NNEM) mesh of polycaprolactone (PCL)-chitosan (CH) prepared by the electrospinning technique was the subject of a controlled release study of soluble DS in water [ 13 ]. Because of the very slow degradation of nanofiber mats, these authors suggested that DS is released either by diffusion or by permeation through DS-NNEMs structure.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the nanofiber net’s slow degradation, the release was mostly governed by diffusion or permeation. The cell viability and imaging data indicate that NIH 3T3 cells experienced no toxicity in the DLF- nanonets structures [ 32 ]. Most of these studies carried in the near past are based on the release and toxicity study of the DLF loaded polymeric systems.…”
Section: Introductionmentioning
confidence: 99%